PASTORAL CARE BAGI NARAPIDANA SEBAGAI WUJUD GEREJA YANG MENAMPILKAN WAJAH KRISTUS DI RUTAN MAKALE - Tangke Layukan, Anastasia; Ria Tana, Eva; Tania, Gabrilia; Victor; Valentin Brai Jawan, Marlyano (Sekolah Tinggi Kateketik dan Pastoral Rantepao (STIKPAR) Toraja, 2023)
Prisoners need attention and care from others. Pastoral care is a form of attention and service provided to prisoners. This article discusses pastoral care for inmates at Class II B Makale State Detention Center. This study uses qualitative methods by conducting observation and interview techniques. This study aims to determine the benefits of pastoral care for inmates at the Makale Detention Center. Pastoral care can assist prisoners in overcoming the problems they experience and can regenerate trust in God so that they are encouraged to improve and renew themselves to become better human beings.